Protecting Personal Information. - Yin Pumin (Beijing Review, 2012)
The article reports on the problem of personal information theft and trading in China. A report on the poor computer security situation in the country was released by the China Center for Information Industry Development (CCID) on March 15, 2012. The proliferation of computer hacking incidents in the country has prompted some actions, such as drafting of personal information protection guidelines.